2013
DOI: 10.1016/s0140-6736(12)61960-6
|View full text |Cite
|
Sign up to set email alerts
|

Extra-couple HIV transmission in sub-Saharan Africa: a mathematical modelling study of survey data

Abstract: Summary Background The proportion of heterosexual HIV transmission in Sub-Saharan Africa that occurs within cohabiting partnerships, as opposed to among single people, or in extra-couple relationships, is a subject of active debate. This question is of immediate importance. As plans to use antiretroviral drugs as a strategy for population-level prevention progress, understanding the importance of different transmission routes is critical to targeting intervention efforts. Methods We built a mechanistic HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 30 publications
7
40
0
Order By: Relevance
“…Up to 27% of transmission events in the HPTN052 and Partners Study were attributable to external events [19, 67]. In a recent modeling study of extra-couple HIV transmission in sub-Saharan Africa, researchers estimated that 27 to 61% of all HIV infections among men and 21 to 51% of infections among women were attributable to extra-couple events [68]. Second, couples may not want to start ART early.…”
Section: Preventing Hiv Transmission Within Serodiscordant Couplesmentioning
confidence: 99%
“…Up to 27% of transmission events in the HPTN052 and Partners Study were attributable to external events [19, 67]. In a recent modeling study of extra-couple HIV transmission in sub-Saharan Africa, researchers estimated that 27 to 61% of all HIV infections among men and 21 to 51% of infections among women were attributable to extra-couple events [68]. Second, couples may not want to start ART early.…”
Section: Preventing Hiv Transmission Within Serodiscordant Couplesmentioning
confidence: 99%
“…This is largely possible by allowing for concurrency: unlike most compartmental models, we can model HIV transmission potential within a heterosexual couple that starts as concordant-negative, then becomes discordant because of an outside partnership, then becomes concordant-positive. 26 Our stochastic methods also improve on the predominant deterministic modelling methods by providing a range of plausible outcomes associated with each scenario, including the predicted extinction probability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that a moderate to large proportion of new heterosexually acquired HIV infections occur within marriage or stable relationships (Bellan et al 2013; Chemaitelly et al 2014; Dunkle et al 2008; Matovu 2010; UNAIDS 2010), and serodiscordant couples are more common than seroconcordant HIV-positive couples (De Walque 2007). Serodiscordant couples can arise from extramarital partnerships but also from premarital partners and prior marriages.…”
Section: Literature Reviewmentioning
confidence: 99%